Hydraulic Evaluation of Urban Drainage System for Flash Floods in Abeokuta, Nigeria - Sobowale, A,; Adegbenro, E. D,; Mustapha, A. T., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Flash floods are rapid-onset floods typically caused by intense rainfall over a short period, often exacerbated by factors like urbanization and deforestation. This study presents a hydraulic evaluation of the urban drainage system in Olorunsogo, Abeokuta, Ogun State, focused on assessing its capacity and efficiency. Measurements of the width, depth, and length of the drains were conducted to determine their total volume. The system's adequacy was evaluated using a drain ratio, which compares the drain volume to the catchment area's runoff volume, expressing the system's capacity to manage runoff. The study found that the total volume is estimated at 46,094.09 m3. The drainage system could only accommodate a limited portion of runoff generated over time. Within one hour, it could handle 32.06%, increasing to 64.13% after two hours, and reaching 96.2% in three hours. However, a significant volume of runoff, up to 737,505.44 m3, would still overwhelm the system in heavy rainfall events lasting over three hours, leading to potential flooding. The study highlights the limitations of the urban drainage system in Olorunsogo, Abeokuta, Ogun State, in managing runoff, particularly during heavy rainfall events. Appropriate recommendation such as implementing floodplain evacuation and a 200 m setback limit, demolishing buildings in high-risk areas, and redesigning the drainage system for improved flash flood management were given for practical adaptation.